1983
DOI: 10.7326/0003-4819-99-2-169
|View full text |Cite
|
Sign up to set email alerts
|

Disease from Infection withVibrio mimicus, A Newly RecognizedVibrioSpecies

Abstract: Clinical and epidemiologic characteristics of disease associated with a newly described nonhalophilic Vibrio species, Vibrio mimicus, were identified by studying isolates from 21 patients referred to the Centers for Disease Control between 1977 and 1981. Two isolates were from the ears of patients with otitis who had recently been exposed to seawater. Nineteen isolates were from stool samples; these patients generally had diarrhea, nausea, vomiting, and abdominal cramps, with fever, headache, and bloody diarrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
52
0
2

Year Published

1985
1985
2006
2006

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(54 citation statements)
references
References 12 publications
0
52
0
2
Order By: Relevance
“…The organisms are recognized as a causative agent of human diarrhoea [1,2]. Clinical studies on V. mimicus infection revealed that diarrhoea was accompanied in the majority of patients by vomiting and abdominal cramps, some with bloody diarrhoea [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The organisms are recognized as a causative agent of human diarrhoea [1,2]. Clinical studies on V. mimicus infection revealed that diarrhoea was accompanied in the majority of patients by vomiting and abdominal cramps, some with bloody diarrhoea [2].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies on V. mimicus infection revealed that diarrhoea was accompanied in the majority of patients by vomiting and abdominal cramps, some with bloody diarrhoea [2]. Gastroenteritis due to V. mimicus has occurred following ingestion of seafoods [1,2]. Some V. mimicus strains have been reported to produce toxins similar to cholera enterotoxin (CT) [3] and heat-stable enterotoxin (ST) [4].…”
Section: Introductionmentioning
confidence: 99%
“…Vibrio mimicus is a closely related species with Vibrio cholerae, and has been reported to be associated with gastrointestinal infections (8,9,12,26). Although extraintestinal infections of these vibrios have also been reported in some cases (2,12,26), most of the investigations have been focused on their role in enteric infections, and factors associated with, or the mechanisms of pathogenicity in extraintestinal infections have not been investigated.…”
mentioning
confidence: 99%
“…Although extraintestinal infections of these vibrios have also been reported in some cases (2,12,26), most of the investigations have been focused on their role in enteric infections, and factors associated with, or the mechanisms of pathogenicity in extraintestinal infections have not been investigated. V. cholerae has been reported to produce an extracellular metalloprotease (11) which has subsequently been shown to be responsible for nicking and activating cholera toxin (3) and therefore recog- nized as a potential in the virulence of the pathogen.…”
mentioning
confidence: 99%
“…
Vibrio mimicus is a potential enteric pathogen that was reported to produce diarrhea sometimes and was also found to be associated with some extra-intestinal infections namely otitis media and wound infection (10,37). It has been proposed that production of multiple toxins or toxic substances is characteristic of this species (7,20,36,38).
…”
mentioning
confidence: 99%